Caracterização da cobertura superficial em encosta na Bacia do Rio das Pombas, Guarapuava PR: bases para entendimento da gênese erosiva em túneis - Silva, Wellington Barbosa da (2011)
On the Guarapuava Plateau/Palmas, in a low slope hillside of superficial covering from basaltic origins, on the right bank of the Rio das Pombas, Paraná state, processes of tunnel erosion (pipes) were identified. These are subsuperficial erosion processes with typical features, such as subsidence of the tunnel roof and rebate structures, which tend to evolve to superficial features. The emerging of this erosive process depends on a set of factors, being the main one, the properties of the superficial covering, such as: texture, macroporosity, granulometric composition (chemical matter make-up), density, porosity e chemical elements that make up the matter, those concerning the hydrological conditions and the topography of the hillside. In order to recognize and characterize the superficial covering in the sector of low hillside, sieve analysis was used, as well as real and apparent density, total porosity verified; toposequences were made and X-ray scattering techniques performed. The results showed that the matter which covers the low hillside sector, where the tunnels are, have a sandy texture due to the properties of microagregation generated by clay mineral, gibbsite; leaving the matter with a high porosity level, thus favoring the flowing of water through subsurfaces. The generated flows tend to be exfiltrated to a ditch wall-like surface, which causes the removal of small particles of matter (seepage). With the opening of small gullies through subsurface, the flow tend to become concentrated (tunnel scour) and consequently enlarge the subsuperficial channels by the mechanical action of the water. In a sequence of factors that can be used for the analysis of the process generation, which causes: alteration in basalt rocks, microaggregation of the matter, macroporosity and increase of water flow through subsurface. Therefore, the hydrology conditions in the hillside contributed for erosion mechanisms to emerge in subsurface, development of erosion process, formation of subsuperficial erosion and, ultimately, superficial erosion process development. These both chemical and physical features found in such field of study, show that the superficial covering is a determining factor for the subsuperficial tunnel erosion to originate in the hillside.